Contractional deformation of porous sandstone: Insights from the Aztec Sandstone, SE Nevada, USA. (May 2015) - Fossen, Haakon; Zuluaga, Luisa F.; Ballas, Gregory; Soliva, Roger; Rotevatn, Atle
Abstract: Contractional deformation of highly porous sandstones is poorly explored, as compared to extensional deformation of such sedimentary rocks. In this work we explore the highly porous Aztec Sandstone in the footwall to the Muddy Mountain thrust in SE Nevada, which contains several types of deformation bands in the Buffington tectonic window: 1) Distributed centimeter-thick shear-enhanced compaction bands (SECBs) and 2) rare pure compaction bands (PCBs) in the most porous parts of the sandstone, cut by 3) thin cataclastic shear-dominated bands (CSBs) with local slip surfaces. Geometric and kinematic analysis of the SECBs, the PCBs and most of the CSBs shows that they formed during ∼E–W (∼100) shortening, consistent with thrusting related to the Cretaceous to early Paleogene Sevier orogeny of the North American Cordilleran thrust system. Based on stress path modeling, we suggest that the compactional bands (PCBs and SECBs) formed during contraction at relatively shallow burial depths, before or at early stages of emplacement of the Muddy Mountains thrust sheet. The younger cataclastic shear bands (CSBs, category 3), also related to E–W Sevier thrusting, are thinner and show larger shear offsets and thus more intense cataclasis, consistent with the initiation of cataclastic shear bands in somewhat less porous materials. Observations made in this work support earlier suggestions that contraction lead to more distributed band populations than what is commonly found in the extensional regime, and that shear-enhanced compaction bands are widespread only where porosity (and permeability) is high. Highlights: We examined the effect of contraction and overthrusting on porous sandstone. Sevier orogenic contraction of Aztec Sandstone created deformation bands. Shear enhanced compaction bands (SECBs) formed early in high porosity layers. SECBs are cut by cataclastic shear bands that probably formed after deeper burial. Bands are distributed, and not clustered into zones that develop into faults.